2023
DOI: 10.1177/08850666231158547
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of COVID-19 Survivors Treated in Intensive Care Unit—Prospective Observational Study

Abstract: Purpose: To investigate the quality of life (QoL) of survivors from severe forms of COVID-19 treated in the ICU. Methods: In this study, we investigated the QoL of patients with severe COVID-19 treated in the ICU from November 2021 to February 2022. In the study period, 288 patients were treated in ICU and 162 were alive at the time of analysis. Of those, 113 patients were included in this study. QoL was analyzed 4 months after ICU admission using the EQ-5D-5L questionnaire administered by telephone. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, in the second survey, the percentage of participants who experienced anxiety did not decrease significantly. Some studies have yielded similar results [30,[34][35][36]. Hoque et al [35] reported that symptoms of COVID-19 could affect the quality of life and emotional well-being of patients who have recovered from COVID-19.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, in the second survey, the percentage of participants who experienced anxiety did not decrease significantly. Some studies have yielded similar results [30,[34][35][36]. Hoque et al [35] reported that symptoms of COVID-19 could affect the quality of life and emotional well-being of patients who have recovered from COVID-19.…”
Section: Discussionmentioning
confidence: 83%
“…However, some studies have reported contradictory results [34][35][36][37]. These studies conducted a cross-sectional survey on discharged patients who had severe COVID-19 symptoms and required hospitalization in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between disease severity and the risk of development of PASC [19]. Persistence of symptoms of PASC subsequently impairs the QoL of COVID-19 survivors [5][6][7][8][9][10]. If PASC develops, the mental component of QoL is affected to the same or even to a greater extent than the physical component [10,11].…”
Section: Pathophysiological Backgroundmentioning
confidence: 99%
“…COVID-19 survivors also have a higher risk of developing severe cardiovascular, pulmonary, neurological, and psychiatric diseases, which may further impair their physical and mental health [4]. Persistence of symptoms affects the quality of life (QoL) of COVID-19 survivors, and the extent of the impact of COVID-19 sequelae on QoL correlates with the number and severity of persistent symptoms [5][6][7][8][9][10]. This affects both the physical and mental health of COVID-19 survivors.…”
Section: Introductionmentioning
confidence: 99%